The Classification into ‘Philological Categories’ of the Qurʾānic Fragments handed down in the Coranus Graecus. A Categorization into Verbatim Citations, Free Citations, Paraphrases, and Allusions - Ulbricht, Manolis (De Medio Aevo, 2023)
The article suggests a uniform system for the categorization of translated passages of the Qurʾān from Arabic into another language. The classification into four so-called ‘Philological Categories’ is based on criteria reflecting the linguistic relationship between the source and target languages in terms of their grammar, syntax, and semantics used therein. The categorization relies on a previous research approach further developing it by defining four categories: Verbatim Quotation, Free Quotation, Paraphrase, and Allusion. The paper first gives definitions for each ‘Philological Category’ (section 2). The system of categorization is then tested (section 3) on the basis of the Greek translation of the Qurʾān Coranus Graecus (9th century terminus ante quem), thus dating back to the time of the Graeco-Arabic translation movement. Several examples are given and borderline cases are critically discussed to illustrate the suggested systematization (section 3.1–4). The study aims, on the one hand, at an in-depth comparative study of Greek and Arabic philologies in order to put, on the other hand, an overall methodological approach up for discussion how Qurʾānic translations may be categorized philologically. A theoretical framework considering the philological context of translated passages will ensure a more appropriate and context-based interpretation of texts pertaining to the Graeco-Arabica period. Thus, the article wishes to engage further discussion on how the philological relation between Greek and Arabic text(s) (passages) might be systematized in a more homogeneous way to allow more source-based conclusions of the respective texts.